Analisis muatan high order thinking skills pada instrumen penilaian pembelajaran tematik di buku guru sekolah dasar - Herdianingsih, Dinda; Sukarno, Sukarno; Yulisetiani, Septi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This study aims to analyze the intensity of the HOTS content in the second grade teacher book theme 7 "Togetherness" and the fourth grade teacher book theme 1 "The Beauty of Togetherness". This research is a qualitative research with the type of document analysis. The data sources of this research are the thematic learning assessment instruments in the second grade teacher book theme 7 "Togetherness" and the fourth grade teacher book theme 1 "The Beauty of Togetherness". The data collection technique used in this research is a documentary study. The data validity test technique used triangulation techniques and increased persistence. Data analysis techniques used the interactive model of Milles and Hubberman with the stages of data collection, data reduction, data presentation and conclusions. The results of this study are the assessment instruments in the class II teacher's book theme 7 "Togetherness" with the HOTS category, namely a total of 12 instruments or 27.3% of the total number of assessment instruments. The assessment instrument in the fourth grade teacher's book theme 1 "The Beauty of Togetherness" with the HOTS category is 17 instruments or 51.5% of the total number of assessment instruments.